Utilization of Digital Forensics in Proving the Crime of Disseminating Indecent Videos Through Facebook Social Media in the Legal Area of West Kalimantan Police - Awaka, M Qahar; Alhadiansyah, Alhadiansyah (Fakultas Hukum Dehasen, 2023)
The research entitled: